Rationalize and reduce costs using the integration of (ABC, RCA, TC) - Nama Haddad, Haneen Amer; Humeedi Alkaabi, Buthaina R. (Opción, 2019)
The study aims at distinguishing between the concepts of rationalization and reduction of costs and shedding light on the classification of strategic manage- ment accounting methods that guide and reduce the costs and the possibility of integrating these methods in order to help organizations reduce their costs and direct their activities towards the customer while highlighting the role of integration between strategic cost management methods in achieving The advantage of cost leadership in the light of the application of the strategy of leadership in the cost in the organization where the approach was taken in the hypothetical theoretical side and the use of the method of extrapolation in the applied side, was selected the General Company for Leather and Textile Industries The study concluded with a set of conclusions, the most important of which is the separation between the concepts of rationalization and reduc- tion of costs and the existence of a complementary relationship between the method (ABC) and (RCA) (TC) and the goal of one is to rationalize the costs of activities after calculation, management and analysis, To the real reduction of costs and according to the target market price.